The Evolution of job lock in the U.S.: Evidence from the affordable care act - James Bailey; Gregory Colman; Dhaval Dave (Journal of Risk and Financial Management, 2022)
Since at least the early 1990s, economists have found substantial evidence of "job lock" in the United States: workers who get health insurance from their employer are less likely to switch jobs. Early work showed stronger job lock among groups that place a higher value on health insurance, whereas more recent work has focused on measuring the effect of specific policies on job lock. We combine these approaches by replicating some of the classic group comparisons (job switching among the more versus less healthy, and among those whose spouses do or do not have their own health insurance) over a much longer time period, using data from the Current Population Survey and the Medical Expenditure Panel Survey. This enables us to document the evolution of job lock over time, with a particular focus on how it changed when policies such as the Affordable Care Act (ACA) took effect. Estimates based on a difference-in-differences methodology indicate that job lock remains substantial, and that ACA has not significantly affected job mobility.
Keywords: 650; Affordable Care Act (ACA); employer sponsored insurance; ESI; health insurance; job lock; job mobility; pre-existing health conditions; spouse